Monomeric alkyne-stabilized complexes of organo−copper(I) and −silver(I) - Lang, Heinrich; Köhler, Katrin; Rheinwald, Gerd; Zsolnai, Laszlo; Büchner, Michael; Driess, Alexander; Huttner, Gottfried; Strähle, Joachim (Organometallics, 1999)
The synthesis of heterobimetallic {[Ti](C⋮CR1)2}MX {[Ti] = (η5-C5H4SiMe3)2Ti; M = Cu, R1 = SiMe3:  4a, X = SCF3; 4b, X = SEt; M = Ag, R1 = tBu:  5a, X = OC(O)Me; 5e, X = NO3; M = Ag, R1 = SiMe3:  5b, X = OC(O)Me; 5c, X = OC(O)Ph; 5d, X = NO3} is described. These compounds together with {[Ti](C⋮CR1)2}CuX (4c, R1 = SiMe3, X = SC6H4CH2NMe2-2; 4d, R1 = tBu, X = SC6H4CH2NMe2-2) can be used for the preparation of a large variety of different organo−copper(I) and −silver(I) species. The titanium−copper complexes {[Ti](C⋮CR1)2}CuR2 [R1 = SiMe3:  6a, R2 = C6F5; 6b, R2 = C6H2(CF3)3-2,4,6; 6c, R2 = C6H2Ph3-2,4,6; R1 = tBu:  6d, R2 = C6H2Ph3-2,4,6; 7, R2 = Me] are accessible by the reaction of 4c or 4d with suitable organic nucleophiles. Monomeric organo−silver(I) compounds can be prepared by using different starting materials:  While the silver(I) aryls {[Ti](C⋮CSiMe3)2}AgR2 [8a, R2 = C6H2(CF3)3-2,4,6; 8b, R2 = C6H2Ph3-2,4,6] are only available by the reaction of 5b with LiC6H2(CF3)3-2,4,6 or BrMgC6H2Ph3-2,4,6, the silver(I) methyl species {[Ti](C⋮CR1)2}AgMe (9a, R1 = SiMe3; 9b, R1 = tBu) can be synthesized by using 5a, 5b, 5d, or 5e as starting materials. While compounds 6−8 are stable under the reaction conditions applied, 9a already starts to decompose at low temperature:  The heterobimetallic titanium−silver acetylide {[Ti](C⋮CSiMe3)(C⋮CAg)}2 (10) is formed by nucleophilic substitution of one of the alkynyl Me3Si groups, whereby SiMe4 is eliminated. Moreover, compounds 6−9 react with Br2 to produce R2−Br along with {[Ti](C⋮CR1)2}MBr (M = Cu; 11a, R1 = tBu; 11b, R1 = SiMe3; M = Ag, 11c, R1 = SiMe3), which yield with equimolar amounts of LiR2 or BrMgR2 the starting materials 6−9 back.The solid-state structures of 4a, 5c, 6c, and 8b are reported. All complexes contain a monomeric (η2-alkyne)2M(η1-X) (4, 5) or (η2-alkyne)2M(η1-R2) (6−9) entity in which the group 11 metal atom M is trigonally coordinated by the two alkynyl ligands C⋮CR1 and the η1-bonded groups X or R2, respectively.